2018
DOI: 10.3171/2016.11.jns161140
|View full text |Cite
|
Sign up to set email alerts
|

Early low cerebral blood flow and high cerebral lactate: prediction of delayed cerebral ischemia in subarachnoid hemorrhage

Abstract: OBJECTIVE Delayed cerebral ischemia (DCI) following subarachnoid hemorrhage (SAH) is one of the major contributors to poor outcome. It is crucial to be able to detect early signs of DCI to prevent its occurrence. The objective of this study was to determine if low cerebral blood flow (CBF) measurements and pathological microdialysis parameters measured at the bedside can be observed early in patients with SAH who later developed DCI. METHODS The authors included 30 patients with severe SAH. The CBF measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
(41 reference statements)
0
31
0
2
Order By: Relevance
“…One critical process that could lead to DCI is hypoxic-ischemic brain damage, which might be caused by vascular events including cerebral vasospasm, microvessel thrombosis, and microvascular dysfunction (Milner et al, 2015;Mutoh et al, 2017;Wagner et al, 2013). Biomarkers related to inflammatory reaction (Chamling et al, 2017), microthrombosis (Boluijt, Meijers, Rinkel, & Vergouwen, 2015), cerebral metabolism (Rostami et al, 2018), and brain injury might be used to predict occurrence of DCI in aSAH patients (Jung, Lange, Zimmermann, & Seifert, 2013). However, technologies such as detection of related biomarkers may eventually be used in goal-oriented therapy, with the aim of creating an optimal physiological environment for the comatose injured brain.…”
Section: Discussionmentioning
confidence: 99%
“…One critical process that could lead to DCI is hypoxic-ischemic brain damage, which might be caused by vascular events including cerebral vasospasm, microvessel thrombosis, and microvascular dysfunction (Milner et al, 2015;Mutoh et al, 2017;Wagner et al, 2013). Biomarkers related to inflammatory reaction (Chamling et al, 2017), microthrombosis (Boluijt, Meijers, Rinkel, & Vergouwen, 2015), cerebral metabolism (Rostami et al, 2018), and brain injury might be used to predict occurrence of DCI in aSAH patients (Jung, Lange, Zimmermann, & Seifert, 2013). However, technologies such as detection of related biomarkers may eventually be used in goal-oriented therapy, with the aim of creating an optimal physiological environment for the comatose injured brain.…”
Section: Discussionmentioning
confidence: 99%
“…DCI typically occurs between the fourth and tenth day after bleeding but its pathophysiology remains yet unclear. Nevertheless, various pathological phenomena such as oxidative stress, cortical spreading depolarizations, microvascular thrombosis and disbalances in cerebral microcirculation are known to be involved in its development 1,2 . On the other hand, the role of vasospasm in DCI appearance is nowadays controversial.…”
mentioning
confidence: 99%
“…However, the L/P ratio was not significantly correlated with CBF. We have recently reported on high lactate and low CBF during the acute phase following SAH in patients who later developed DCI ( 26 ). Different studies report on different levels of CBF thresholds for ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In an additional study, comatose patients following head injury were compared to normal subjects and CBF threshold of 55.3 ml/100 g/min was defined as hyperemia ( 28 ). Our recent report on patients suffering severe SAH showed that patients who later develop DCI have initial low CBF levels of 23.7 ml/100 g/min compared to 37.5 ml/100 g/min in those who do not develop DCI ( 26 ). Current results are in line with previous findings and emphasize the important role of lactate in correlation with CBF in patients suffering SAH.…”
Section: Discussionmentioning
confidence: 99%